The Economic Impact of the Road Infrastructure Utilization and the Consumption of Electrical Energy in the Kedungsepur Urban Area - Widjonarko, Widjonarko; Ul Fikri, Auliya (Universitas Negeri Semarang, 2023)
Kedungsepur is a national urban area located in the northern region of Java Island, comprising of six autonomous regions: Semarang City as the principal urban center, along with Kendal Regency, Semarang Regency, Salatiga City, Grobogan Regency, and Demak Regency as supporting areas. Kedungsepur holds significant economic importance in Central Java, contributing approximately 24% to the total Gross Regional Domestic Product (GRDP) over the past two decades. To strengthen Kedungsepur 's role in the regional economy, the government has invested in infrastructure, aiming to bolster the overall economy in Central Java, particularly in the northern region. Therefore, it is important to assess the economic impact of providing infrastructure in the Kedungsepur area to determine the extent to which infrastructure contributes to the regional economy. To measure the economic impact of infrastructure in Kedungsepur, this research uses a regression model with panel data and uses GRDP data as the dependent variable, and infrastructure utilization, especially road utilization and electricity consumption as independent variables. To ensure that regional economic growth in Kedungsepur is influenced by the existence of infrastructure, this research also uses household consumption data as a control variable. The research results show that regional economic growth in Kedungsepur is not only influenced by infrastructure utilization, but also household consumption. Among these, road usage emerges as the primary contributor to the economic growth of the Kedungsepur region, surpassing the impact of electricity consumption and household spending